1959
DOI: 10.1002/hlca.19590420320
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse de la Phé2‐oxytocine

Abstract: Rac. 2-dehydro-emetine (XV) and rac. 2-dehydro-isoemetine (XVI) have been synthcsizcd in fivc steps and in good yicld from 2-oxo-3-ethyl-9,10-dimethoxy-l, 2,3, 4,6, . Homologues and analogues of XV and XVI with other substituents have been obtained in the same way.Rac. 2-dchydro-emetine (XV) and its analogucs with other substituents in the isoquinoliiie part exhibit high activity in infections caused by Entanaoeba histolytica. The compounds substitutcd in %position with groups other than an ethyl and all dcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

1960
1960
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…There are two lines of evidence that aromaticity is important. First, it has been experimentally shown that the replacement of tyrosine by phenylalanine (both having an aromatic ring on the side chain) at position 2 of oxytocin has little effect on the oxytocic activity of the peptide (Jaquenoud and Boissonnas 1959;Boissonnas and Guttmann 1960), but the replacement by serine (lacking the aromatic ring) reduces the oxytocic activity to an undetectable level . Second, substitution models based on Grantham's distance or Miyata's distance, neither of which takes aromaticity into consideration, invariably overestimate nonsynonymous substitutions involving codons coding for aromatic amino acids (our unpublished results).…”
Section: Amino Acid Properties and Evolution Of The Genetic Codementioning
confidence: 99%
“…There are two lines of evidence that aromaticity is important. First, it has been experimentally shown that the replacement of tyrosine by phenylalanine (both having an aromatic ring on the side chain) at position 2 of oxytocin has little effect on the oxytocic activity of the peptide (Jaquenoud and Boissonnas 1959;Boissonnas and Guttmann 1960), but the replacement by serine (lacking the aromatic ring) reduces the oxytocic activity to an undetectable level . Second, substitution models based on Grantham's distance or Miyata's distance, neither of which takes aromaticity into consideration, invariably overestimate nonsynonymous substitutions involving codons coding for aromatic amino acids (our unpublished results).…”
Section: Amino Acid Properties and Evolution Of The Genetic Codementioning
confidence: 99%
“…The Cornell group has synthetized various analogues of oxytocin [Ressler & (31,32,33) and Rudinger et at. (34) have also synthesized analogues of oxytucin.…”
Section: Oxytocin and Vasopressinmentioning
confidence: 99%
“…Phenylalanine2-oxytocin, in which the phenolic hydroxyl group of oxytocin has been removed, was prepared independently by Bodansky & du Vigneaud (1959) and Jaquenoud & Boissonnas (1959). Both groups of workers found an oxytocic potency, measured on the isolated rat uterus, of 30 u./mg.…”
Section: Discussionmentioning
confidence: 99%